Outcome between Laparoscopic and Open Ventral Hernia Repair: a Quasi-experimental Study - Yadav, Rohit Prasad; Gautam, Manish; Bhattarai, Amit; Adhikari, Dinesh; Sah, Sachidanand; Paudyal, Nabin (Journal of BP Koirala Institute of Health Sciences, 2022)
Background: The debate on the best surgical approach to ventral hernia repair continues. We compared the outcomes of laparoscopic with open ventral hernia repair in terms of post-operative pain, recovery and patients’ satisfaction on cosmesis.Methods: This quasi-experimental study allocated 70 participants scheduled for ventral hernia repair into laparoscopic and open repair (allocation 1:1) from July 2020 to July 2021. The primary outcome included VAS for pain at 24, 48 and 72 hours after surgery. The secondary outcomes included duration of surgery and hospital stay, time to return to normal activity, patients’ satisfaction on cosmesis and recurrence rate.Results: The age, gender distribution, and size of hernia defect were comparable between the groups (p > 0.05). Post-operative VAS scores (median, IQR) were similar at 24 hours (7, 6 - 8 vs.7, 6 - 7, p > 0.99) and 48 hours (4, 3 - 5 vs. 4, 3 - 4, p > 0.99) and lesser in laparoscopic group at 72 hours (1, 1 - 2 vs. 2, 2 - 2, p < 0.001) after surgery. The duration of surgery (mean ± SD) was longer (105.14 ± 34.88 vs. 87.49 ± 29.13 minutes, p = 0.02) while duration of hospital stay was shorter (4.80 ± 3.08 vs. 6.66 ± 2.94 days, p = 0.01) and return to normal activity was earlier (6.89 ± 2.93 vs. 15.40 ± 5.65 days, p < 0.001) in laparoscopic group.Conclusion: Laparoscopic ventral hernia repair was associated with lesser post-operative pain at 72 hours, early post-operative recovery as well as better patients’ satisfaction on cosmesis as compared to open procedure.